Energy-Saving Driving for a Flexible Manipulator by Utilizing Micro Fiber Composite - Akira Abe (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2022)
In this paper, we examine a point-to-point motion task of a flexible manipulator with macro fiber composite (MFC) and then propose a new feedforward control method to suppress driving energy and residual vibration simultaneously. For this, we use an MFC attached to one side of the flexible manipulator that has one revolute joint as an actuator. We attempt to express the joint angle in the control technique by combining cycloidal and polynomial functions. On the other hand, the input voltage profile of the MFC is expressed using Gaussian functions. The trajectory of the joint angle and the input voltage profile are dependent upon the coefficients of the polynomial function and the Gaussian functions, respectively. The trajectory and the input voltage profile are optimized simultaneously to cancel the residual vibration under saving energy by tuning the coefficients using the particle swarm optimization algorithm. The effectiveness of the proposed method is verified by performing simulations and experiments. Thus, our findings confirmed that the simultaneous optimization of the trajectory of the joint angle and the input voltage of the MFC saves more energy than only the optimization of the trajectory. Therefore, we could establish an energy-saving feedforward control method by driving two actuators.